First Order Seismic Microzonation of Miri district of Sarawak Malaysia using AHP-GIS Platform - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Hasmida, Hamza; Norazzlina, M.Sa'don; Azrin, Ahmad (The Mattingley Publishing Co., Inc., 2020)
This investigation is dealing with the seismic microzonation index of Miri district of Sarawak Malaysia using Analytical Hierarchy Process (AHP) by utilizing Geographical Information System (GIS), Miri is the coastal city situated in the Sarawak state of Malaysia. This study is timely for the prevention of havoc since, Peninsular Malaysia lies in the vicinity of regions (Sumatra, Indonesia) that have experienced strong earthquakes in the past. The state of Sarawak and Sabah, also lie in Malaysia are nearby to the seismic tremor zone of South Philippines and North Sulawesi. However, the chances of being vibrated by at least moderate local earthquakes are highly possible from the previous earthquake records of Malaysia. The highest PGA for Sarawak is 0.09g (which is in Miri) and the lowest is 0.01g in terms of 10% probability of exceedance of an event in 50 years. The hazard themes consist of peak ground acceleration (PGA), shear wave velocity (Vs30), liquefaction potential index (LPI), amplification ratio AR, lithology (LTGY) and predominant frequency (PF), which were developed for the Miri district. All the hazard themes were integrated in the GIS environment using AHP, in order to produce the seismic microzonation index map. From the results, the Miri district has been classified into three zones viz, Low, Moderate and High hazard zone. The current study predominantly reports issues to develop the seismic microzonation map of Miri city and the results of this study can be used as direct data in choosing the proper land use planning in order to reduce the adverse effects of earthquakes in the Miri district of Sarawak, Malaysia.